Prevalence and Predictors of Persistent Symptoms After Clearance of SARS-CoV-2 Infection: A Multicenter Study from Egypt - Khalaf M; Alboraie M; Abdel-Gawad M; Abdelmalek M; Abu-Elfatth A; Abdelhamed W; Zaghloul M; ElDeeb R; Abdeltwab D; Abdelghani M; El-Raey F; Aboalam H; et al. (Infection and Drug Resistance, 2022)
Marwa Khalaf,1 Mohamed Alboraie,2 Muhammad Abdel-Gawad,3 Mohamed Abdelmalek,4 Ahmed Abu-Elfatth,4 Walaa Abdelhamed,5 Mariam Zaghloul,6 Rabab ElDeeb,7 Doaa Abdeltwab,4 Mohamed Abdelghani,4 Fathiya El-Raey,8 Hani Aboalam,1 Azza Badry,9 Mina Tharwat,10 Shima Afify,11 Doaa Elwazzan,7 Ahmed Shawkat Abdelmohsen,4 Hayam Fathy,12 Shaker Wagih Shaltout,13 Helal F Hetta,14 Shamardan E Bazeed15 1Assiut Liver Center, Ministry of Health, Assiut, 71515, Egypt; 2Department of Internal Medicine, Al-Azhar University, Cairo, Egypt; 3Hepatology, Gastroenterology and Infectious Diseases Department, Al-Azhar University, Assiut, Egypt; 4Tropical Medicine and Gastroenterology Department, Assiut University, Assiut, Egypt; 5Tropical Medicine and Gastroenterology Department, Sohag University Hospital, Sohag, Egypt; 6Hepatology, Gastroenterology and Infectious Diseases Department, Kafr El-Sheikh University, Kafr El-Sheikh, Egypt; 7Tropical Medicine Department, Alexandria University, Alexandria, Egypt; 8Hepatogastroenterology and Infectious Diseases Department, Al-Azhar University, Damietta, Egypt; 9Epidemiologist, Infectious Disease Control Department Preventive Medicine Assiut Health Affairs Directorate, Assiut, Egypt; 10Tropical Medicine and Gastroenterology Department, Aswan University, Aswan, Egypt; 11Gastroenterology Department, National Hepatology and Tropical Medicine Research Institute, Cairo, Egypt; 12Internal Medicine, Hepatogastroenterology Unit, Assiut University, Assiut, Egypt; 13Tropical Medicine Department, Port Said University, Port Said, Egypt; 14Department of Medical Microbiology and Immunology, Faculty of Medicine, Assiut University, Assiut, 71515, Egypt; 15Tropical Medicine and Gastroenterology Department, South Valley University, Qena, EgyptCorrespondence: Marwa Khalaf, Assiut liver center, Ministry of health, Assiut, 71515, Egypt, Email Marwa.Kh@med.aun.edu.eg Helal F Hetta, Department of Medical Microbiology and Immunology, Faculty of Medicine, Assiut University, Assiut, 71515, Egypt, Email helalhetta@aun.edu.egBackground and Aim: Little is known about the persistence of symptoms after clearance of SARS-CoV-2 infection. Our study aimed to assess persistent symptoms in COVID-19 patients after clearance of SARS-CoV-2 infection.Methodology: A multi-center survey was conducted on first wave COVID-19 patients with confirmed SARS-CoV-2 infection. Sociodemographic and clinical characteristics, including presenting symptoms and persistent symptoms after viral clearance and possible factors contributing to persistence of such symptoms, were collected using an online multicomponent questionnaire. Descriptive and inferential statistical analysis was performed to detect the most persisting symptoms and factors contributing to their persistence.Results: Overall, 538 patients were enrolled. Mean age was 41.17 (±SD 14.84), 54.1% were males, and 18.6% were smokers. Hypertension and diabetes were the most reported co-morbidities. Mild symptoms were reported in 61.3% of patients, 51.3% were admitted to hospital and 6.5% were admitted to the intensive care unit. Our study identified 49 types of persisting symptoms. Fatigue (59.1%), sense of fever (46.5%), anorexia (24.3%) and diarrhea (24.3%) were the most commonly reported persisting symptoms followed by loss of taste and smell (22.3%), headache (21.4%), cough (20.8) and dyspnea (21%). The use of hydroxychloroquine, azithromycin and multivitamins were significantly associated with persistence of symptoms (OR = 8.03, 8.89 and 10.12, respectively).Conclusion: Our study revealed that in COVID-19 recovered patients, many patients reported persistence of at least one symptom, particularly fatigue and sense of fever. Follow-up of patients after discharge from hospital is recommended until complete resolution of symptoms.Keywords: coronavirus, COVID-19, SARS-CoV-2, fatigue, dyspnea